Neuroendocrinology and Psychiatric Disorder - Brown, Gregory M., M.D. Ph.D. (New York, 1984)
Neuroendocrine Abnormalities in Schizophrenia. Pharmacoendocrinology of Schizophrenia. Is Prolactin a Marker for Brain Dopamine Function. Overview of Endocrynology of Stress. Classification and Description of Stress....